Reminiscence Computer Therapy for People with Dementia - Černý, Martin; Šlajchrt, Zbyněk; Pecinovský, Rudolf, 1954-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2016)
The aim of this diploma thesis is to implement a presentation layer for the Reminiscence Computer Therapy application. Reminiscence Therapy involves the discussion of the past memories and it is believed to help people with dementia to improve their well-being and sustain their memories. Computer Reminiscence Therapy involves technology in this therapy. The research introduces into Dementia and Reminiscence Therapy with and without using technologies. The application developed as part of this diploma thesis uses picture upload and speech recognition techniques for the memory input. This is used to support remembering of past memories and to increase discussion. The application can be used with or without the carer as well as with friends and family members. The six most important requirements on the developed application are the speech recognition, picture upload, asking questions about the previous recordings, asking questions about tagged friends, using old stories for discussion and presenting the statistics. The application was developed as a part of the competition made by AngelHack organization. Presentation, business and persistence layers of the application are discussed in this diploma thesis as well as user manual and persistence layer implementation of the requirements. The presentation layer was developed using React framework for JavaScript. Other libraries have to be used as well with the most important being Redux library for storing application state. This library affected the structure of the persistence layer.
Vedoucí práce: Zbyněk Šlajchrt
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses